Multi-component alloy magnetic powder core composite material and preparation method thereof
By coating heavy metal oxides and aqueous silicon sols on the multi-alloy magnetic powder and sealing the secondary insulating agent, the problems of complex process, high cost and insufficient magnetic performance in the prior art are solved, and efficient and low-cost multi-alloy magnetic powder core composite material are achieved, improving the magnetic properties and oxidation resistance of the material.
Patent Information
- Application Number
- CN202311426137.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
AI Technical Summary
In the prior art, when preparing multi-alloy magnetic powder core composite materials, the process is complex and the cost is high, and the magnetic and oxidation resistance of the material is insufficient, resulting in high losses and poor superposition characteristics.
The multi-alloy magnetic powder is coated by mixing heavy metal oxides and aqueous silicon sols to form a thin and uniform insulating layer, and a dense cladding layer is formed by sealing the holes by secondary insulating agent.
The process operation is simplified, process costs are reduced, and the magnetic properties and oxidation resistance of the material are improved. The product has a stable Q value, high resistivity and low loss.
Smart Images

Figure BDA0004522268110000121 
Figure BDA0004522268110000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal soft magnetic materials, and in particular relates to a multi-element alloy magnetic powder core composite material and a preparation method thereof. Background Art
[0002] Metal soft magnetic powder core is a composite material made of ferromagnetic metal powder after insulation treatment, and then evenly mixed with auxiliary medium and pressed. It has a large saturation magnetization intensity Bs and good DC superposition characteristics. It has good application prospects in electronic fields such as inverters and vehicle power supplies with complex working conditions and increasingly high DC voltages. The saturation magnetic induction intensity (Bs) of metal soft magnetic powder core is higher than that of ferrite materials, which can meet the needs of device miniaturization, but its disadvantages are low magnetic permeability and high high-frequency loss. Sendust aluminum magnetic powder core has the lowest loss among composite soft magnetics, and iron-nickel magnetic powder core has the highest Bs. The combination of the two can achieve the complementary advantages of high Bs, high superposition and low loss, and the application field is greatly extended.
[0003] For example, patent CN105063486A proposes a method for manufacturing FeNi material with a magnetic permeability of 100, wherein 90wt% to 99wt% FeNi and 1wt% to 10wt% ZnCu powder are mixed into a coarse powder, and a premixed FeNi composite material is obtained by mixing evenly in a ball mill, and an insulating medium and a release agent are added to the powder material, and after molding and heat treatment, the FeNi material is obtained. This material solves the coating problem of FeNi alloy, but its loss is relatively high, and the insulating material is not suitable for Sendust aluminum alloy magnetic powder, and there is no possibility of adding Sendust aluminum to reduce the loss. Patent CN107578874A proposes a method for preparing an iron-nickel magnetic powder core with a magnetic permeability of 200, including: the magnetic powder is first coated with an inorganic oxide, then annealed (anti-oxidation protective atmosphere), then passivated with phosphoric acid, and an adhesive (water glass, potassium silicate or silica gel water) is added, and finally a release agent is mixed to form and heat-treat the product; the magnetic permeability manufactured by the invention exceeds 200, but the loss is high (20% higher than the normal value at 100kHz), the superposition characteristics at 50Oe are relatively poor, and the process is relatively complicated. The insulation method of the invention is suitable for the coating of iron-silicon-aluminum alloys, but the magnetic powder needs to be coated with inorganic materials and annealed first, and an anti-oxidation protective atmosphere is also required, which increases the process difficulty and process cost.
[0004] Sendust and FeNi are materials with completely different chemical properties. The surfaces of the two alloy magnetic powders are uniformly coated with a layer of insulating material, which puts higher requirements on the coating materials and coating process. Because the oxidation resistance of Sendust and FeNi is different after insulation coating, the heat treatment temperature and atmosphere of the magnetic core must be different. The two powders are compounded together, and the heat treatment conditions are kept consistent with those of single FeNi, which will inevitably increase the cost. The process is more complicated when the two powders are insulated and then compounded together. In the end, the two powders are mixed and the processing conditions and environment tend to be harsh.
[0005] Therefore, how to simplify process operations, reduce process costs, and improve the magnetic properties and antioxidant properties of materials is a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a multi-component alloy magnetic powder core composite material and a preparation method thereof. The present invention uses multi-component alloy magnetic powder as a substrate, first coats the substrate with metal acid and nanosol, adds a thin and uniform insulating layer, and then uses a secondary insulating agent to seal the substrate, so that the surface of the magnetic powder that is not adsorbed to the oxide is further coated, and finally a thin, uniform and dense coating layer is formed on the surface of the substrate. The method is simple in process and low in cost. The multi-component alloy magnetic powder core composite material prepared based on the method has high molding density, good oxidation resistance of the insulating layer, stable product Q value and high resistivity.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a multi-element alloy magnetic powder core composite material, the preparation method comprising the following steps:
[0009] (1) mixing heavy metal oxides and aqueous silica sol to obtain a primary insulating agent solution;
[0010] (2) mixing the primary insulating agent solution and the multi-element alloy magnetic powder, performing a primary insulating treatment, and obtaining a primary product;
[0011] (3) mixing the primary product with a secondary insulating agent solution and performing a secondary insulation treatment to obtain a secondary product;
[0012] (4) The secondary product is subjected to molding treatment and heat treatment in sequence to obtain the multi-component alloy magnetic powder core composite material.
[0013] In the present invention, the heavy metal oxide is mixed with the aqueous silica sol to dissolve the heavy metal oxide to form a metal acid, which is then mixed with the silica sol to form a dispersed low-grade acid.
[0014] As a preferred technical solution of the present invention, the heavy metal oxide in step (1) includes chromic anhydride and / or permanganic anhydride.
[0015] Preferably, the weight of the heavy metal oxide in step (1) is 0.25-1% of the weight of the multi-component alloy magnetic powder, for example, it can be 0.25%, 0.5%, 0.75% or 1%.
[0016] In the present invention, if the weight of the heavy metal oxide is too large, the acidity will be too large and the reaction will be violent; if the weight of the heavy metal oxide is too small, the reaction will be insufficient and the thickness of the insulating layer will not be dense.
[0017] Preferably, the weight of the aqueous silica sol in step (1) is 1.5-10% of the weight of the multi-element alloy magnetic powder, for example, it can be 1.5%, 3%, 4.5%, 6%, 7.5%, 9% or 10%.
[0018] In the present invention, if the weight of the aqueous silica sol is too large, the amount of sol is too large, resulting in insufficient reaction of the metal acid; if the weight of the aqueous silica sol is too small, the metal oxide cannot be fully dissolved, resulting in excessive local reaction.
[0019] Preferably, the mixing time in step (1) is 1-3 min, for example, 1 min, 1.5 min, 2 min, 2.5 min or 3 min.
[0020] As a preferred technical solution of the present invention, the multi-element alloy magnetic powder in step (2) includes iron-nickel magnetic powder and sendust magnetic powder.
[0021] Preferably, the mesh sizes of the iron-nickel magnetic powder and the sendust magnetic powder are independently 250-500 meshes, for example, 250 meshes, 300 meshes, 400 meshes or 500 meshes.
[0022] Preferably, in the multi-element alloy magnetic powder, the volume content of particles with a particle size of 20-55 μm is greater than 95%.
[0023] As a preferred technical solution of the present invention, the mixing process in step (2) is accompanied by stirring.
[0024] Preferably, the mixing time in step (2) is 5-10 min, for example, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min.
[0025] Preferably, the temperature of the primary insulation treatment in step (2) is 80-150°C, for example, it can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C.
[0026] In the present invention, if the temperature of the primary insulation treatment is too low, the drying is insufficient and the density is insufficient; if the temperature of the primary insulation treatment is too high, agglomeration is likely to occur.
[0027] Preferably, the time for the insulation treatment in step (2) is 5-10 minutes, for example, it can be 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes.
[0028] As a preferred technical solution of the present invention, the secondary insulating agent solution in step (3) includes an organic solvent and a secondary insulating agent.
[0029] Preferably, the weight ratio of the organic solvent to the secondary insulating agent is (3-5):1, for example, it can be 3:1, 3.5:1, 4:1, 4.5:1 or 5:1.
[0030] Preferably, the weight of the secondary insulating agent in step (3) is 0.5-3.5% of the weight of the multi-element alloy magnetic powder, for example, it can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or 3.5%.
[0031] In the present invention, if the weight of the secondary insulating agent is too large, the fluidity is poor; if the weight of the secondary insulating agent is too small, the compactness is insufficient.
[0032] Preferably, the secondary insulating agent includes any one of organic silicon resin, phosphoric acid, aluminum dihydrogen phosphate or silicone resin, or a combination of at least two thereof, preferably phosphoric acid or organic silicon resin.
[0033] It should be noted that the silicone resin is a highly cross-linked polyorganosiloxane with a network structure, usually a mixture of methyltrichlorosilane, dimethyldichlorosilane, phenyltrichlorosilane, diphenyldichlorosilane or methylphenyldichlorosilane.
[0034] Preferably, the organic solvent comprises acetone and / or methyl acetate.
[0035] As a preferred technical solution of the present invention, the mixing process in step (3) is accompanied by stirring.
[0036] Preferably, the mixing time in step (3) is 2-5 min, for example, it can be 2 min, 2.5 min, 3 min, 3.5 min, 4 min, 4.5 min or 5 min.
[0037] Preferably, the temperature of the secondary insulation treatment in step (3) is 80-150°C, for example, it can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C.
[0038] Preferably, the time for the secondary insulation treatment in step (3) is 3-5 minutes, for example, 3 minutes, 4 minutes or 5 minutes.
[0039] As a preferred technical solution of the present invention, the specific steps of the molding process in step (4) include:
[0040] The secondary product and a release agent are mixed to prepare magnetic powder to be formed, and then the magnetic powder to be formed is pressed into shape.
[0041] Preferably, the weight of the release agent is 0.3-0.4% of the weight of the secondary product, for example, it can be 0.3%, 0.32%, 0.34%, 0.36%, 0.38% or 0.4%, etc.
[0042] Preferably, the release agent comprises aluminum stearate and / or stearic acid amide.
[0043] Preferably, during the compression molding, the pressure applied by the press is 17-20 tons / cm 2 , for example, it can be 17 tons / cm 2 , 18 tons / cm 2 , 19 tons / cm 2 or 20 tons / cm 2 wait.
[0044] As a preferred technical solution of the present invention, the heat treatment in step (4) is carried out in a protective atmosphere, and the gas in the protective atmosphere includes nitrogen.
[0045] Preferably, the temperature of the three heat treatments in step (4) is 680-780°C, for example, 680°C, 700°C, 720°C, 740°C, 760°C or 780°C.
[0046] Preferably, the time for the three heat treatments in step (4) is 25-90 min, for example, it can be 25 min, 35 min, 45 min, 55 min, 65 min, 75 min, 85 min or 90 min.
[0047] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0048] (I) mixing iron-nickel magnetic powder with a mesh size of 250-500 meshes and sendustine magnetic powder with a mesh size of 250-500 meshes to obtain multi-element alloy magnetic powder;
[0049] Among them, the volume content of particles with a particle size of 20-55 μm is greater than 95%;
[0050] (II) adding heavy metal oxide to aqueous silica sol and stirring to dissolve for 1-3 minutes to obtain a primary insulating agent solution;
[0051] The weight of the heavy metal oxide is 0.25-1% of the weight of the multi-component alloy magnetic powder, and the weight of the aqueous silica sol is 1.5-10% of the weight of the multi-component alloy magnetic powder;
[0052] (III) stirring and mixing the primary insulating agent solution and the multi-component alloy magnetic powder for 5-10 minutes, and performing a primary insulating heat treatment at a temperature of 80-150° C. for 5-8 minutes to obtain a primary product;
[0053] (IV) adding a secondary insulating agent into an organic solvent and stirring to dissolve the mixture to obtain a secondary insulating agent solution;
[0054] The weight of the secondary insulating agent is 0.5-3.5% of the weight of the multi-element alloy magnetic powder, and the weight ratio of the organic solvent to the secondary insulating agent is (3-5):1;
[0055] (V) stirring and mixing the primary product and the secondary insulating agent solution for 2-5 minutes, and performing a secondary insulation treatment at 80-150° C. for 5-8 minutes to obtain a secondary product;
[0056] (VI) mixing the secondary product with a release agent to prepare magnetic powder to be formed, and then pressing the magnetic powder to be formed into a magnetic powder blank by a press;
[0057] The weight of the release agent is 0.3-0.4% of the weight of the multi-element alloy magnetic powder;
[0058] (VII) In a nitrogen atmosphere, heat treating the magnetic powder blank at 680-780° C. for 25-90 min to obtain a multi-component alloy magnetic powder core composite material.
[0059] In a second aspect, the present invention provides a multi-component alloy magnetic powder core composite material, wherein the multi-component alloy magnetic powder core composite material is prepared by the preparation method described in the first aspect;
[0060] The multi-component alloy magnetic powder core composite material comprises multi-component alloy magnetic powder and a coating layer coated on the surface of the multi-component alloy magnetic powder, wherein the coating layer comprises a nano-oxide inner insulating layer and an outer insulating layer.
[0061] It should be noted that a part of the secondary insulating agent further insulates the surface of the magnetic powder that is not adsorbed to the nano-oxide, and the other part forms an outer insulating layer, which effectively increases the resistivity of the magnetic powder and reduces eddy current loss.
[0062] Preferably, the coating layer has a thickness of 1-1.5 μm, for example, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm or 1.5 μm.
[0063] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0064] Compared with the prior art, the present invention has the following beneficial effects:
[0065] The present invention uses multi-element alloy magnetic powder as a substrate, first coats the substrate with metal acid and nanosol to add a thin and uniform insulating layer, and then uses a secondary insulating agent to seal the substrate, so that the surface of the magnetic powder that is not adsorbed to the oxide is further coated, and finally a thin, uniform and dense coating layer is formed on the surface of the substrate. The method is simple in process and low in cost. The multi-element alloy magnetic powder core composite material prepared based on the method has high molding density, low loss, good insulation layer oxidation resistance, stable product Q value and high resistivity. DETAILED DESCRIPTION
[0066] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0067] Example 1
[0068] This embodiment provides a method for preparing a multi-element alloy magnetic powder core composite material, the preparation method comprising the following steps:
[0069] (1) 400 g of 250-mesh iron-nickel magnetic powder and 600 g of 300-mesh sendust magnetic powder were mixed evenly to obtain multi-element alloy magnetic powder;
[0070] Among them, the volume content of particles with a particle size of 20-55 μm is greater than 95%;
[0071] (2) Add 3 g of heavy metal oxide to 20 g of aqueous silica sol (Jiangfeng Chemical, Type II) and stir to dissolve for 2 min to obtain a primary insulating agent solution;
[0072] The heavy metal oxide is chromic anhydride, the weight of the heavy metal oxide is 0.3% of the weight of the multi-component alloy magnetic powder, and the weight of the aqueous silica sol is 2% of the weight of the multi-component alloy magnetic powder;
[0073] (3) adding the primary insulating agent solution to 1000 g of multi-element alloy magnetic powder, stirring and mixing for 8 min, then transferring to a heating container, and performing a primary insulating treatment (i.e., heating and drying) at a temperature of 120° C. for 30 min to obtain a primary product;
[0074] (4) adding 7 g of a secondary insulating agent to 21 g of an organic solvent and stirring to dissolve the mixture to obtain a secondary insulating agent solution;
[0075] Among them, the secondary insulating agent is silicone resin (Shenzhen Jinwangxing, a new insulating agent), the organic solvent is acetone, the weight of the secondary insulating agent is 0.7% of the weight of the multi-element alloy magnetic powder, and the weight ratio of the organic solvent to the secondary insulating agent is 3:1;
[0076] (5) adding the secondary insulating agent solution to the primary product, stirring and mixing for 5 minutes, and then transferring to a heating container, performing a secondary insulation treatment (i.e., heating and drying) at 120° C. for 40 minutes to obtain a secondary product;
[0077] (6) mixing the secondary product with 4 g of a release agent to prepare magnetic powder to be formed, and then pressing the magnetic powder to be formed into a magnetic powder blank (outer diameter 26.9 mm, inner diameter 14.7 mm, height 11.2 m) by a hydraulic press;
[0078] The release agent is aluminum stearate powder, the weight of the release agent is 0.4% of the weight of the multi-element alloy magnetic powder, and the pressure applied by the hydraulic press is 19 tons / cm 2 ;
[0079] (7) In a nitrogen atmosphere, the magnetic powder blank is heat treated at 680° C. for 25 min to obtain a multi-component alloy magnetic powder core composite material.
[0080] This embodiment also provides a multi-component alloy magnetic powder core composite material, which is prepared by the above-mentioned preparation method;
[0081] The multi-component alloy magnetic powder core composite material comprises multi-component alloy magnetic powder and a coating layer coated on the surface of the multi-component alloy magnetic powder, wherein the coating layer comprises a nano-oxide inner insulating layer and an outer insulating layer;
[0082] The coating layer has a thickness of 1.3 μm.
[0083] Example 2
[0084] This embodiment provides a method for preparing a multi-element alloy magnetic powder core composite material, the preparation method comprising the following steps:
[0085] (1) 400 g of 500-mesh iron-nickel magnetic powder and 600 g of 250-mesh sendust magnetic powder were mixed evenly to obtain multi-element alloy magnetic powder;
[0086] Among them, the volume content of particles with a particle size of 20-55 μm is greater than 95%;
[0087] (2) Add 3 g of heavy metal oxide to 20 g of aqueous silica sol (Jiangfeng Chemical, Type II) and stir to dissolve for 2 min to obtain a primary insulating agent solution;
[0088] The heavy metal oxide is chromic anhydride, the weight of the heavy metal oxide is 0.3% of the weight of the multi-component alloy magnetic powder, and the weight of the aqueous silica sol is 2% of the weight of the multi-component alloy magnetic powder;
[0089] (3) adding the primary insulating agent solution to 1000 g of multi-element alloy magnetic powder, stirring and mixing for 8 min, then transferring to a heating container, and performing a primary insulating treatment (i.e., heating and drying) at a temperature of 120° C. for 30 min to obtain a primary product;
[0090] (4) adding 5 g of a secondary insulating agent into 20 g of an organic solvent and stirring to dissolve the mixture to obtain a secondary insulating agent solution;
[0091] The secondary insulating agent is phosphoric acid (Wuxi Jingke, purity> 99.5%), the organic solvent is acetone, the weight of the secondary insulating agent is 0.5% of the weight of the multi-element alloy magnetic powder, and the weight ratio of the organic solvent to the secondary insulating agent is 4:1;
[0092] (5) adding the secondary insulating agent solution to the primary product, stirring and mixing for 3 minutes, then transferring to a heating container, and performing a secondary insulation treatment (i.e., heating and drying) at 100° C. for 30 minutes to obtain a secondary product;
[0093] (6) mixing the secondary product with 4 g of a release agent to prepare magnetic powder to be formed, and then pressing the magnetic powder to be formed into a magnetic powder blank (outer diameter 26.9 mm, inner diameter 14.7 mm, height 11.2 m) by a hydraulic press;
[0094] The release agent is aluminum stearate powder, the weight of the release agent is 0.4% of the weight of the multi-element alloy magnetic powder, and the pressure applied by the hydraulic press is 19 tons / cm 2 ;
[0095] (7) In a nitrogen atmosphere, the magnetic powder blank is heat treated at 680° C. for 25 min to obtain a multi-component alloy magnetic powder core composite material.
[0096] This embodiment also provides a multi-component alloy magnetic powder core composite material, which is prepared by the above-mentioned preparation method;
[0097] The multi-component alloy magnetic powder core composite material comprises multi-component alloy magnetic powder and a coating layer coated on the surface of the multi-component alloy magnetic powder, wherein the coating layer comprises a nano-oxide inner insulating layer and an outer insulating layer;
[0098] The coating layer has a thickness of 1.5 μm.
[0099] Example 3
[0100] The difference between this embodiment and embodiment 1 is that the mass of the heavy metal oxide in step (2) is 15 g, that is, the weight of the metal oxide is 1.5% of the weight of the multi-component alloy magnetic powder.
[0101] The rest of the preparation methods and parameters were the same as those in Example 1.
[0102] Example 4
[0103] The difference between this embodiment and embodiment 1 is that the mass of the heavy metal oxide in step (2) is 2 g, that is, the weight of the oxide is 0.2% of the weight of the multi-component alloy magnetic powder.
[0104] The rest of the preparation methods and parameters were the same as those in Example 1.
[0105] Example 5
[0106] The difference between this embodiment and embodiment 1 is that the mass of the aqueous silica sol in step (2) is 150 g, that is, the weight of the aqueous silica sol is 15% of the weight of the multi-element alloy magnetic powder.
[0107] The rest of the preparation methods and parameters were the same as those in Example 1.
[0108] Example 6
[0109] The difference between this embodiment and embodiment 1 is that the mass of the aqueous silica sol in step (2) is 10 g, that is, the weight of the aqueous silica sol is 1% of the weight of the multi-component alloy magnetic powder.
[0110] The rest of the preparation methods and parameters were the same as those in Example 1.
[0111] Comparative Example 1
[0112] This comparative example provides a method for preparing a multi-element alloy magnetic powder core composite material, the preparation method comprising the following steps:
[0113] (1) 400 g of 250-mesh iron-nickel magnetic powder and 600 g of 300-mesh sendust magnetic powder were mixed evenly to obtain multi-element alloy magnetic powder;
[0114] Among them, the volume content of particles with a particle size of 20-55 μm is greater than 95%;
[0115] (2) Prepare 1.5 g of silane coupling agent (KH550), add it to 5 g of acetone, stir for 3 min to completely dissolve, and obtain a silane coupling agent solution;
[0116] The weight of the silane coupling agent is 0.15% of the weight of the multi-element alloy magnetic powder.
[0117] (3) Add the prepared coupling agent solution to 1000g of magnetic powder, stir rapidly for 8min, dry naturally for 1h, and then heat it in a kiln with nitrogen atmosphere at 810℃ for 30min. Then turn off the heating and wait until the powder temperature drops to room temperature before taking it out for use.
[0118] (4) Prepare 14 g of phosphoric acid (Wuxi Jingke, purity > 99.5%), add it to 40 g of acetone to dissolve, and obtain a phosphoric acid solution. Then take 0.3 g of chromic anhydride and add it to the phosphoric acid solution. After rapid stirring and dissolving, obtain a coating solution for standby use.
[0119] The weight of phosphoric acid is 1.4% of the weight of the multi-component alloy magnetic powder, and the weight of chromic anhydride is 0.03% of the weight of the multi-component alloy magnetic powder;
[0120] (5) adding the coating liquid to the magnetic powder product obtained in step (3), rapidly stirring for 3 minutes, and then transferring to a heating container for drying for 30 minutes at a temperature of 100° C. to obtain a coated product;
[0121] (6) Prepare 8 g of silicone resin (Huzhou Jianuo, high temperature type resin), dissolve it in 20 g of acetone to obtain a silicone resin solution, then add the silicone resin solution to the coated product in step (5), stir quickly, then take it out, spread it flat and dry it naturally for 8 hours, then mix the obtained product with 4 g of release agent aluminum stearate powder to prepare magnetic powder to be formed, and then use a hydraulic press to make the magnetic powder to be formed into a magnetic powder core blank (outer diameter 26.9 mm, inner diameter 14.7 mm, height 11.2 m);
[0122] The weight of aluminum stearate powder accounts for 0.4% of the weight of multi-element alloy magnetic powder. The pressure applied by the hydraulic press is 19 tons / cm 2
[0123] (7) In a nitrogen atmosphere, the magnetic powder blank is subjected to a heat preservation treatment at 680° C. for 25 minutes to obtain a multi-component alloy magnetic powder core composite material.
[0124] Performance Testing
[0125] The multi-component alloy magnetic powder core composite materials prepared in the above examples and comparative examples were coated with epoxy resin coatings and then subjected to electrical performance tests.
[0126] The test conditions are as follows: winding the core, with 20 turns for the primary coil and the secondary coil respectively, using the inductor LCR CH3303 to test the inductance and convert it into magnetic permeability; using an AC BH meter to test the total loss at different frequencies under the conditions of a load of 100mT, a frequency of 50kHz and 100kHz; testing the DC superposition characteristics; winding the core with 25 turns of copper wire (wire diameter 0.4mm), using the inductor LCR CH3303 to test the quality factor Q value at a test frequency of 100kHz and a level voltage of 1V.
[0127] The test results are shown in Table 1.
[0128] Table 1
[0129]
[0130]
[0131] analyze:
[0132] As can be seen from the above table, the present invention uses multi-element alloy magnetic powder as the substrate, first coats the substrate with heavy metal oxides, adds a thin and uniform insulating layer, and then uses a secondary insulating agent to seal the substrate, so that the surface of the magnetic powder that is not adsorbed to the oxide is further coated, and finally a thin, uniform and dense coating layer is formed on the surface of the substrate. The method is simple in process and low in cost. The multi-element alloy magnetic powder core composite material prepared based on the method has high molding density, good insulation layer oxidation resistance, stable product Q value, and high resistivity.
[0133] It can be seen from the data results of Example 1, Example 2 and Comparative Example 1 that the present invention adds heavy metal oxide sol to aqueous silica sol to form a composite coating solution, which is easily dispersed and evenly coated on the surface of iron-nickel and iron-silicon-aluminum micropowders. A simple drying treatment can form a highly dense insulating layer on the surface of the magnetic powder. Finally, the magnetic ring and other samples made of the magnetic powder core material have low loss, which is 15% lower than that of the sample given in Comparative Example 1. At the same time, the absolute value of the DC superposition characteristic increases by 3-4%, and the improvement effect is quite significant.
[0134] The applicant declares that the present invention is explained by the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a multi-element alloy magnetic powder core composite material, characterized in that: The preparation method comprises the following steps: (1) mixing heavy metal oxides and aqueous silica sol to obtain a primary insulating agent solution; (2) mixing the primary insulating agent solution and the multi-element alloy magnetic powder, performing a primary insulating treatment, and obtaining a primary product; (3) mixing the primary product with a secondary insulating agent solution and performing a secondary insulation treatment to obtain a secondary product; (4) The secondary product is subjected to molding treatment and heat treatment in sequence to obtain the multi-component alloy magnetic powder core composite material.
2. The preparation method according to claim 1, characterized in that: The heavy metal oxide in step (1) comprises chromic anhydride and / or permanganic anhydride; Preferably, the weight of the heavy metal oxide in step (1) is 0.25-1% of the weight of the multi-component alloy magnetic powder; Preferably, the weight of the aqueous silica sol in step (1) is 1.5-10% of the weight of the multi-element alloy magnetic powder; Preferably, the mixing time in step (1) is 1-3 min.
3. The preparation method according to claim 1 or 2, characterized in that: The multi-element alloy magnetic powder in step (2) includes iron-nickel magnetic powder and sendust magnetic powder; Preferably, the mesh sizes of the iron-nickel magnetic powder and the sendust magnetic powder are independently 200-500 meshes; Preferably, in the multi-element alloy magnetic powder, the volume content of particles with a particle size of 20-55 μm is greater than 95%.
4. The preparation method according to any one of claims 1 to 3, characterized in that The mixing process in step (2) is accompanied by stirring; Preferably, the mixing time in step (2) is 5-10 min; Preferably, the temperature of the primary insulation treatment in step (2) is 80-150° C. Preferably, the time for the insulation treatment in step (2) is 5-10 minutes.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The secondary insulating agent solution in step (3) comprises an organic solvent and a secondary insulating agent; Preferably, the weight ratio of the organic solvent to the secondary insulating agent is (3-5):1; Preferably, the weight of the secondary insulating agent in step (3) is 0.5-3.5% of the weight of the multi-element alloy magnetic powder; Preferably, the secondary insulating agent comprises any one of organic silicon resin, phosphoric acid, aluminum dihydrogen phosphate or silicone resin or a combination of at least two thereof, preferably phosphoric acid or organic silicon resin; Preferably, the organic solvent comprises acetone and / or methyl acetate.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The mixing process in step (3) is accompanied by stirring; Preferably, the mixing time in step (3) is 2-5 min; Preferably, the temperature of the secondary insulation treatment in step (3) is 80-150° C. Preferably, the time for the secondary insulation treatment in step (3) is 3-5 minutes.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The specific steps of the molding process in step (4) include: The secondary product is mixed with a release agent to prepare magnetic powder to be formed, and then the magnetic powder to be formed is pressed into shape; Preferably, the weight of the release agent is 0.3-0.4% of the weight of the secondary product; Preferably, the release agent comprises aluminum stearate and / or stearic acid amide; Preferably, during the compression molding, the pressure applied by the press is 17-20 tons / cm 2 .
8. The preparation method according to any one of claims 1 to 7, characterized in that: The heat treatment in step (4) is carried out in a protective atmosphere, wherein the gas in the protective atmosphere comprises nitrogen; Preferably, the temperature of the heat treatment in step (4) is 680-780°C; Preferably, the heat treatment time in step (4) is 25-90 min.
9. The preparation method according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: (I) mixing iron-nickel magnetic powder with a mesh size of 250-500 meshes and sendustine magnetic powder with a mesh size of 250-500 meshes to obtain multi-element alloy magnetic powder; Among them, the volume content of particles with a particle size of 20-55 μm is greater than 95%; (II) adding heavy metal oxide to aqueous silica sol and stirring to dissolve for 1-3 minutes to obtain a primary insulating agent solution; The weight of the heavy metal oxide is 0.25-1% of the weight of the multi-component alloy magnetic powder, and the weight of the aqueous silica sol is 1.5-10% of the weight of the multi-component alloy magnetic powder; (III) stirring and mixing the primary insulating agent solution and the multi-element alloy magnetic powder for 5-10 minutes, and performing a primary insulating treatment at a temperature of 80-150° C. for 5-10 minutes to obtain a primary product; (IV) adding a secondary insulating agent into an organic solvent and stirring to dissolve the mixture to obtain a secondary insulating agent solution; The weight of the secondary insulating agent is 0.5-3.5% of the weight of the multi-element alloy magnetic powder, and the weight ratio of the organic solvent to the secondary insulating agent is (3-5):1; (V) stirring and mixing the primary product and the secondary insulating agent solution for 2-5 minutes, and performing a secondary insulating treatment at 80-150° C. for 3-5 minutes to obtain a secondary product; (VI) mixing the secondary product with a release agent to prepare magnetic powder to be formed, and then pressing the magnetic powder to be formed into a magnetic powder blank by a press; The weight of the release agent is 0.3-0.4% of the weight of the multi-element alloy magnetic powder; (VII) In a nitrogen atmosphere, heat treating the magnetic powder blank at 680-780° C. for 25-90 min to obtain a multi-component alloy magnetic powder core composite material.
10. A composite material of multi-element alloy magnetic powder core, characterized in that: The multi-element alloy magnetic powder core composite material is prepared by the preparation method according to any one of claims 1 to 9; The multi-component alloy magnetic powder core composite material comprises multi-component alloy magnetic powder and a coating layer coated on the surface of the multi-component alloy magnetic powder, wherein the coating layer comprises a nano-oxide inner insulating layer and an outer insulating layer; Preferably, the coating layer has a thickness of 1-1.5 μm.
Citation Information
Patent Citations
Composite FeNi material with magnetic conductivity being 100 and manufacturing method thereof
CN105063486A
Preparation method of iron-nickel magnetic powder core with magnetic permeability mu = 200
CN107578874A